Atmospheric rivers and associated extreme rainfall over Morocco. (13th May 2022) - Khouakhi, Abdou; Driouech, Fatima; Slater, Louise; Waine, Toby; Chafki, Omar; Chehbouni, Abdelghani; Raji, Otmane
Abstract: Atmospheric rivers (ARs) are long, narrow, and transient corridors of enhanced water vapour content in the lower troposphere, associated with strong low‐level winds. These features play a key role in the global water cycle and drive weather extremes in many parts of the world. Here, we assessed the frequency and general characteristics of landfalling ARs over Morocco for the period 1979–2020. We used ECMWF ERA5 reanalysis data to detect and track landfalling ARs and then assessed AR association with rainfall at the annual and seasonal scales, as well as extreme rainfall events (defined as a daily precipitation amount exceeding the 99th percentile threshold of the wet days) at 30 gauging stations located across Morocco. Results indicate that about 36 ARs/year make landfall in Morocco. AR occurrence varies spatially and seasonally with highest occurrences in the autumn (SON) and Winter (DJF) in the northern part of the country and along the Atlantic across northern regions. AR rainfall climatology indicates up to 180 mm·year −1 recorded in stations located in the northwest. High fractional contributions ( 28%) are recorded in the north and the Atlantic regions, with the driest regions of the south receiving about a third of their annual rainfall from ARs. For extreme rainfall, the highest AR contributions can attain over 50% in the southern dry regions and along the Atlantic north coast and Atlas highlands. Abstract : This AR occurred on November 30, 2010 was associated with exceptionally heavy rainfall, causing flooding in many parts of the northwest coastal areas where major urban centres are such as the region of Casablanca, the largest city of the country causing loss of life and significant damage to infrastructure such as bridges and roads. Red dashed line indicates AR extent. AR axis and centroid are shown with a cyan line and black dot, respectively. Blue shading in the background indicates rainfall accumulation exceeding 10 mm for the concurrent and the following day of the AR occurrence.